INFLUENCE OF BOUNDARY LAYER IN THR CROWN BLADE ON SPECIFICATIONS FOR DEGREE OF AXIAL COMPRESSOR - Ластівка, I. (Science-based technologies, 2011)
There are generalized results of researches in the article. Influence of active and passive control of boundary layer on compressor characteristics is shown.